Concurrent neoadjuvant endocrine therapy with chemotherapy in HR+HER2- breast cancer: a systematic review and meta-analysis - Wu, Ping; Lv, Wenjie (Frontiers in Endocrinology, 2024)
The role of simultaneous neoadjuvant endocrine therapy in chemotherapy in HR+HER2- breast cancer continues to be controversial. This systematic review and meta-analysis was conducted to further evaluate the effectiveness and safety of this strategy for HR+HER2- breast cancer patients. Trials in which HR+HER2- breast cancer patients were randomly assigned to either single or simultaneous endocrine-assisted neoadjuvant chemotherapy were eligible for inclusion. The prime endpoint was the pathological complete response （pCR）rate. The clinical response (complete clinical response: CR, partial response: PR) and safety were secondary endpoints. A random effect model was used for statistical analysis. A total of 690 patients from five trials were included. PCR rate was 10.43% in the concomitant endocrine group and 7.83% in control group (OR=1.37，95%CI 0.72-2.60, P=0.34). The CR rate was 15.50% for the concomitant endocrine group and 10.26% for the control group. (OR=1.61，95%CI 0.99-2.61， P=0.05). ORR (CR+PR) was significantly higher in the simultaneous endocrine group compared to the control group (79.53%（272/342）vs. 70.09%（239/341）, OR=1.70，95%CI 1.19-2.43, P=0.004) and the meta-analysis approach showed no heterogeneity（I2=0%, P=0.54）. Tamoxifen concurrent with chemotherapy could increase the frequency of adverse events, whereas aromatase inhibitors (AIs) would not. Our findings provide evidence for the efficacy and safety of concurrent neoadjuvant endocrine therapy (AIs) with chemotherapy as an available option to achieve a higher clinical response rate for HR+HER2- breast cancer patients compared with chemotherapy alone with low toxicity.